2017
DOI: 10.1080/09513590.2017.1409711
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tribulus Terrestris for the treatment of premenopausal women with hypoactive sexual desire disorder: a randomized double-blinded, placebo-controlled trial

Abstract: Although hypoactive sexual desire disorder (HSDD) is the most common sexual complaint, there is no consensus for the ideal treatment. Our study aimed to evaluate the efficacy of treating premenopausal women with HSDD with Tribulus terrestris and its effect on the serum levels of testosterone. We performed a prospective, randomized, double-blind, placebo-controlled trial, with 40 premenopausal women reporting diminished libido, receiving T. terrestris or placebo. The questionnaires FSFI and the QS-F were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
1
19
0
2
Order By: Relevance
“…In oxidative stress, the reactive oxygen species and advanced end glycation products react with nitric oxide in the vasculature forming reactive nitrogen species, contributing to the pathogenesis of erectile dysfunction [80]. Furthermore, different studies have shown that TT extracts are efficient in women with sexual disorders by having a favorable action in clinical trials on hypoactive sexual desire in women, as well as in the control of menopausal transition symptoms [81][82][83].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In oxidative stress, the reactive oxygen species and advanced end glycation products react with nitric oxide in the vasculature forming reactive nitrogen species, contributing to the pathogenesis of erectile dysfunction [80]. Furthermore, different studies have shown that TT extracts are efficient in women with sexual disorders by having a favorable action in clinical trials on hypoactive sexual desire in women, as well as in the control of menopausal transition symptoms [81][82][83].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Puncturevine is one of the most researched aphrodisiac plants known as "plant Viagra", with its therapeutic properties being attributed to the presence of furostanol saponins (Šalamon et al, 2016). Protodioscin is the main phytochemical compound in T. terrestris plants and is suggested to stimulate the production of testosterone in men, while women with hypoactive sexual desire disorder (HSSD) who received T. terrestris exhibited increased levels of testosterone (Vale, Zanolla Dias de Souza, Rezende, & Geber, 2017). In contrast, Antonio et al (2000) reported that oral administration of tribulus (a herbal preparation of T. terrestris) at a dose of 3.21 mg kg −1 body weight, had no significant effect on body composition or exercise performance in resistance-trained subjects.…”
Section: Health Effectsmentioning
confidence: 99%
“…(2018), plasebo grubuna göre Tribulus terrrestries ile tedavi ettikleri kadınlarda cinsel istek, uyarılma, lubrikasyon, orgazm, ağrı, memnuniyet alanlarında iyileşme olduğunu ifade etmişlerdir. [23] Yapılan diğer çalışmalar da, kadın cinsel fonksiyon bozukluklarının tedavisinde etkili ve güvenilir bir uygulama olduğunu göstermektedir. [8,24] Ancak, Tribulus terrestriesin insan cinsel yanıtı üzerindeki etkisinin açık olarak bilinmediği ve kılavuzlarda kullanılacak dozlar hakkında net bir bilginin olmadığı, olumsuz etkilerine ilişkin kanıtların da yeterli olmadığı belirtildiği için uzun vadeli çalışmaların yapılmasının gerekli olduğu üzerinde durulmaktadır.…”
Section: Tribulus Terrestris (Puncture Vine)unclassified